Heat and mass transfer - Baehr, Hans Dieter (Springer Berlin Heidelberg, 2011)
This comprehensive textbook provides a solid foundation of knowledge on the principles of heat and mass transfer and shows how to solve problems by applying modern methods. The basic theory is developed systematically, exploring in detail the solution methods to all important problems. The thoroughly revised 3rd edition includes an introduction to the numerical solution of Finite Elements. A new section on heat and mass transfer in porous media has also been added. The book will be useful not only to upper-level and graduate students, but also to practicing scientists and engineers, offering a firm understanding of the principles of heat and mass transfer, and showing how to solve problems by applying modern methods. Many completed examples and numerous exercises with solutions facilitate learning and understanding, and an appendix includes data on key properties of important substances.